PERKEMBANGAN ANAK DENGAN LETAK SUNGSANG DI KABUPATEN SIDOARJO - Sri Wardini Puji Lestari; Eka Diah Kartiningrum (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2016)
Incomplete Breech pregnancy is a complication during delivery that impact on fetal and maternal. Type of delivery is not exactly result of improper handling and impact on the growth and development of children after a few years of his birth. The purpose of this study was to describe the development of children with a history of incomplete breech pregnancies in Sidoarjo. This study used an observational study, population was children aged 1-3 years with a history of breech delivery based on data from RS Sidoarjo (2014) is a total of 287 children. A large study sample were 62 children aged 1-3 years. Data development were observed using and KPSP. Results of the study explained that children with a history of breech born have normal development, only 8 children have distorted development. There are many factors that affected children development especially about the stimulation that given by parents. Children with Incomplete Breech pregnancy history culd have normal development if they get good stimulation from their parents.